Distinct types of intramitochondrial protein aggregates protect mitochondria against proteotoxic stress - Lea Bertgen; Jan-Eric Bökenkamp; Tim Schneckmann; Christian Koch; Markus Räschle; Zuzana Storchová; Johannes M. Herrmann (Cell Reports, 2024)
Summary: Mitochondria consist of hundreds of proteins, most of which are inaccessible to the proteasomal quality control system of the cytosol. How cells stabilize the mitochondrial proteome during challenging conditions remains poorly understood. Here, we show that mitochondria form spatially defined protein aggregates as a stress-protecting mechanism. Two different types of intramitochondrial protein aggregates can be distinguished. The mitoribosomal protein Var1 (uS3m) undergoes a stress-induced transition from a soluble, chaperone-stabilized protein that is prevalent under benign conditions to an insoluble, aggregated form upon acute stress. The formation of Var1 bodies stabilizes mitochondrial proteostasis, presumably by sequestration of aggregation-prone proteins. The AAA chaperone Hsp78 is part of a second type of intramitochondrial aggregate that transiently sequesters proteins and promotes their folding or Pim1-mediated degradation. Thus, mitochondrial proteins actively control the formation of distinct types of intramitochondrial protein aggregates, which cooperate to stabilize the mitochondrial proteome during proteotoxic stress conditions.